Implementation of Traditional Games in Classical Services: Efforts to Build Social Relationships in Multicultural Students - Okta Sari, Resti; Pahlevi, Reza (Academia Edu Cendekia Indonesia (AEDUCIA), 2022)
This paper aims to describe the benefits of traditional children's games in classical services. This is motivated by a phenomenon of changes in playing activities, which more often use modern games that are identical to the use of technology, which results in starting to become forgotten and become strangers. Writing based on this literature study can illustrate the importance of using traditional games in classical services, which can foster prosocial behavior, increase motivation and provide innovation so that boredom does not occur and makes it easier to understand the material provided in guidance and counseling services.